Surface modification strategies to reinforce the soft tissue seal at transmucosal region of dental implants - Siqi Jin; Yameng Yu; Ting Zhang; Daping Xie; Yufeng Zheng; Chunming Wang; Yunsong Liu; Dandan Xia (Bioactive Materials, 2024)
Soft tissue seal around the transmucosal region of dental implants is crucial for shielding oral bacterial invasion and guaranteeing the long-term functioning of implants. Compared with the robust periodontal tissue barrier around a natural tooth, the peri-implant mucosa presents a lower bonding efficiency to the transmucosal region of dental implants, due to physiological structural differences. As such, the weaker soft tissue seal around the transmucosal region can be easily broken by oral pathogens, which may stimulate serious inflammatory responses and lead to the development of peri-implant mucositis. Without timely treatment, the curable peri-implant mucositis would evolve into irreversible peri-implantitis, finally causing the failure of implantation. Herein, this review has summarized current surface modification strategies for the transmucosal region of dental implants with improved soft tissue bonding capacities (e.g., improving surface wettability, fabricating micro/nano topographies, altering the surface chemical composition and constructing bioactive coatings). Furthermore, the surfaces with advanced soft tissue bonding abilities can be incorporated with antibacterial properties to prevent infections, and/or with immunomodulatory designs to facilitate the establishment of soft tissue seal. Finally, we proposed future research orientations for developing multifunctional surfaces, thus establishing a firm soft tissue seal at the transmucosal region and achieving the long-term predictability of dental implants.